High PRDM16 expression predicts poor outcomes in adult acute myeloid leukemia patients with intermediate cytogenetic risk: a comprehensive cohort study from a single Chinese center. Issue 1 (2nd January 2021) - Dao, Feng-Ting; Chen, Wen-Min; Long, Ling-Yu; Li, Ling-Di; Yang, Lu; Wang, Jun; Liu, Yan-Rong; Jiang, Hao; Zhang, Xiao-Hui; Jiang, Qian; Qin, Ya-Zhen
Abstract: Acute myeloid leukemia with intermediate cytogenetic risk (ICR-AML) needs to be stratified and abnormal gene expression might be prognostic. PR/SET domain 16 ( PRDM16 ) transcript levels were assessed in 267 consecutive adult ICR-AML patients at diagnosis by real-time quantitative PCR. 38.2% patients had PRDM16 transcript levels higher than the upper limit of normal bone marrow samples. Through ROC curve analysis and comparison of relapse-free survival (RFS), the optimal cutoff value of PRDM16 transcript levels was identified to group patients into high expression ( PRDM16 -H, 21.3%) and low expression ( PRDM16 -L). PRDM16 -H was significantly associated with lower 4-year RFS and overall survival (OS) rates in the entire cohort, patients with normal karyotypes, FLT3-ITD (-) and NPM1 mutation (+)/ FLT3-ITD (–) patients (all p < .05). Multivariate analysis showed that PRDM16 -H was an independent adverse prognostic factor for RFS and OS in the entire cohort. Therefore, high PRDM16 expression at diagnosis predicts poor outcomes in adult ICR-AML patients.